Attenuation of pressor response following intubation: Efficacy of nitro-glycerine lingual spray - Indira Kumari; Udita Naithani; Vinod Kumar Dadheech; D S Pradeep; Khemraj Meena; Devendra Verma (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: The role of nitro-glycerine (NTG) lingual spray for attenuation of the hemodynamic response associated with intubation is not much investigated. We conducted this study to evaluate the efficacy of NTG lingual pump or pen spray in attenuation of intubation induced hemodynamic responses and to elucidate the optimum dose. Material and Methods: In a prospective randomized controlled trial, 90 adult patients of ASA I, II, 18-60 year posted for elective general surgery under general anesthesia with intubation were randomly allocated to three groups as Group C (control) - receiving no NTG spray, Group N1 - receiving 1 NTG spray and Group N2 - receiving 2 NTG spray one minute before intubation. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate were recorded at baseline, just before intubation (i.e., 60 s just after induction and NTG spray), immediately after intubation, at 1, 2, 5 and 10 min after intubation. Results: Incidence of hypertension was significantly higher in Group C (60%, n = 18) as compared to Group N1 and N2 (10%, n = 3 each), P < 0.01. Mean value of SBP, DBP and MAP showed a significant rise as compared to baseline, following intubation in control group (15.31% in SBP, 12.12% in DBP, 17.77% in MAP) that persisted till 5 min, while no significant rise was observed in Group N1 and N2. There was a trend toward fall in blood pressure in Group N2 (4.95% fall in SBP, 4.72% fall in MAP) 1-min following spray, which was clinically insignificant. Mean value of SBP, DBP and MAP was significantly higher in Group C than in Group N1, which was in turn greater than Group N2 (Group C > N1> N2), P < 0.05. However, incidence of tachycardia was comparable in three groups (70% in group C, 63.33% in Group N1 and 67.77% in Group N2, P > 0.05). Conclusions: We concluded that the NTG lingual spray in dose of 0.4 mg (1 spray) or 0.8 mg (2 sprays) was effective in attenuation of intubation induced hemodynamic response, in terms of preventing significant rise in SBP, DBP and MAP compared to control group.